CHALLENGES ENCOUNTERED BY THE SELECTED BOOK PRINTING BUSINESS ALONG QUEZON CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examines the "Challenges Encountered by Selected Book Printing Businesses in Quezon City," focusing on the factors that affect their growth and ability to adapt to evolving market demands. Specifically, it aims to analyze the challenges related to sourcing and expanding supplies within the book printing industry, identifying key obstacles and potential strategies for improvement. This study utilizes a mixed-methods research approach, commonly applied in behavioral, health, and social sciences, particularly in multidisciplinary and complex societal research. A descriptive research design was adopted to gather and analyze data on the challenges of expanding supplies in the book printing industry in Quezon City. The researchers selected 15 book printing shops to obtain specific and relevant information. Convenience sampling was employed to select willing and available participants to respond to the survey, ensuring accessible and practical data collection. The findings reveal key challenges faced by book printing businesses in Quezon City, including printing supplies (26% of quality control issues resulting in misprints or defects), resources (38% of printer downtime due to maintenance), and services (34% shortage of personnel). To address these challenges, the study recommends enhancing supply quality, resource management, and workforce efficiency to improve operations and better meet customer expectations. The study highlights the significance of incorporating recycled and eco-friendly materials to expand the book printing supply while offering diverse personalization options for unique designs. It emphasizes the need to prioritize sustainability by utilizing environmentally friendly products and collaborating with responsible producers. The findings serve as a foundation for book printing businesses in Quezon City to enhance their supply chain expansion while promoting sustainable and innovative practices.
Keywords: recycled materials • eco-friendly printing • personalization options • sustainability • book printing industry • supply chain expansion • quality control • resource management • workforce efficiency • quezon city printing businesses